Effect of Direct Current on Solid-Liquid Interfacial Tension and Wetting Behavior of Ga–In–Sn Alloy Melt on Cu Substrate - Limin Zhang; Ning Li; Hui Xing; Rong Zhang; Kaikai Song (Advances in Condensed Matter Physics)
The effect of direct current (DC) on the wetting behavior of Cu substrate by liquid Ga–25In–13Sn alloy at room temperature is investigated using a sessile drop method. It is found that there is a critical value for current intensity, below which the decrease of contact angle with increasing current intensity is approximately linear and above which contact angle tends to a stable value from drop shape. Current polarity is a negligible factor in the observed trend. Additionally, the observed change in contact angles is translated into the corresponding change in solid-liquid interfacial tension using the equation of state for liquid interfacial tensions. The solid-liquid interfacial tension decreases under DC. DC-induced promotion of solute diffusion coefficient is likely to play an important role in determining the wettability and solid-liquid interfacial tension under DC.